Mortality among health-conscious elderly Californians. - Enstrom, J E (1982)
In an attempt to obtain epidemiologic evidence regarding the mortality rate among vitamin supplement users, a prospective study was made of 479 elderly Californian respondents to a 1974 questionnaire carried in Prevention, a health magazine that advocates vitamin supplement usage. Based on self-reported questionnaire data obtained in 1974 and 1977, this cohort does indeed consume large quantities of vitamin and mineral supplements. In addition, the cohort is quite health conscious and appears to have taken up a "Prevention life-style" in recent years. For instance, these individuals are primarily nonsmokers, although about 50% formerly smoked cigarettes. Most of them eat meat, poultry, or fish but do so in moderation; and they consume only modest amounts of alcohol, whole milk, white bread, salt, and sugar. Their socioeconomic status is somewhat higher than the national average. Because this group differs from the general population in many ways it is difficult to separate the various factors that might influence their health. During 6 years of follow-up, a total of 107 deaths occurred. Based on comparison with 1977 United States whites, the standardized mortality ratio (SMR) is 78% for the males, 54% for the females, and 68% for both sexes combined. All three SMR values are significantly less than 100% (P less than 0.05). For both sexes combined, the SMR is 86% for cancer, 62% for total cardiovascular diseases, and 73% for all other causes. Only the cardiovascular SMR is significantly lower than 100%. The death rate for the males is approximately the same as that reported among other healthy nonsmoking questionnaire respondents. but the death rate for females is significantly less (P less than 0.01). The only notable relationships between questions asked in 1974 and subsequent mortality are those indicating a higher mortality rate associated with inactivity, heart trouble, and very low and very high levels of vitamin E intake. For this highly selected cohort, the overall "Prevention life-style" appears to be a healthy one, but the cohort experiences no clear reduction in total mortality because of high levels of vitamin intake per se.